Pengaruh label halal, kualitas layanan online, dan harga terhadap pembelian di Go Food - Zaen, M. Zaenal Abidin (Nur Science Institute, 2023)
This research aims to determine the influence of the halal label, e-service quality, and price on purchasing decisions, with purchase interest as an intervening variable. This research uses a quantitative method by processing primary data through a questionnaire distributed to 100 go-food customers. The data analysis method uses path analysis. The research results show that the halal label variable is insignificant in purchasing decisions, while e-service quality, price, and intention influence purchasing decisions. The halal label and price have a significant positive effect on purchase intention. However, e-service quality is not significant in terms of purchase intention. Meanwhile, e-service quality is insignificant in purchasing decisions, with purchase intention as an intervening variable. Meanwhile, the halal label and price are significant in purchasing decisions, with purchase intention as an intervening variable.